HALAL LIFESTYLE AND ISLAMIC BRANDING TREND (AN EVALUATIVE STUDY OF THE “HALAL PRODUCT BRANDING” STRATEGY OF CHOCOLICIOUS INDONESIA) - Shadriany Saleh; Marhaeni Saleh (Jurnal Dakwah Tabligh, 2021)
This research focuses on how the Halal Product Branding strategy encourages awareness and consumer’s acceptance aspects for culinary products brand produced by PT. Chocolicios Indonesia. The research was conducted using evaluation methods on 2 main aspects, namely: message content and readability measures. The evaluation of message content looks at how messages conveyed through Halal Branding can attract public attention, how the public responds to how to message Halal Product Branding and how the public evaluates the messages carried by the Halal label, whether it’s positive or negative.. The research method used is the evaluative research of public relation program by. Ronald D Smith, and the nature of the research is descriptive research. The approach used is qualitative data techniques in the form of interview with the informant and respondents. Results of this study indicate thatHalal Brand strategy is an effective communication strategy where this strategy enabled Chocolicious to be widely recognized as a producer of good quality halal products, which in turn encourages buyers to be more confident and trust in using or consuming products from Chocolicious Indonesia.